Washback Effect Assessment of MahÄrah IstimÄ' using Google Form - Rahmawati, Rahmawati; Zakiyah, Zaimatuz; Sitompul, Julkhaidir (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
Assessment has specific effects on learning, both positive and negative effects. In this case, assessment should encourage the implementation of better learning. This survey research aims to analyze the positive and negative effects of the mahÄrah istimÄâ€™ assessment using Google Forms or what is also called the washback effect. The respondents in this research were 43 PAI I FTK UIN Imam Bonjol Padang students. In this regard, data was collected through observation techniques, questionnaires, and interviews. As a primary data collection technique, the questionnaire covers three aspects: exam preparation strategies, learning attitudes, and learning materials. Then, the collected data was analyzed using descriptive statistics. The research results show that the total scores for each aspect are 37.4, 3.8, and 3.89, respectively. In other words, these aspects are included in the "excellent" category. Thus, based on these three aspects, the mahÄrah istimÄâ€™ assessment using Google Forms positively impacts learning. This research contributes practically to the experience of the mahÄrah istimÄâ€™Â  test using Google Forms. For future research, explore longitudinal effects, compare assessment methods, and study the sustainability of positive impacts. Also, analyze educators' perspectives and use qualitative data for deeper insights into assessment dynamics and student learning experiences, refining mahÄrah istimÄâ€™ assessment on digital platforms like Google Forms